Connected and concerned: Variation in parents' online safety concerns. Issue 3 (21st October 2013) - boyd, danah; Hargittai, Eszter
Abstract The widespread adoption of social media and other networked technologies by youth has prompted concerns about the safety issues they face when they go online, including the potential of being hurt by a stranger, being exposed to pornographic or violent content, and bullying or being bullied. These concerns often manifest as fears and anxieties in parents and can lead to pervasive moral panics. Eager to shield children from potential risks, parents—and lawmakers—often respond to online safety concerns by enacting restrictions with little consideration for the discrepancy between parental concern and actual harm. As this article shows, parental fears are not uniform across different population groups. Our findings demonstrate that, while concern may be correlated with experiencing online safety risks, parental concerns with respect to online safety issues also vary significantly by background—notably race and ethnicity, income, metropolitan status, and political ideology. As policies develop to empower parents, more consideration must be given to how differences in parental fears shape attitudes, practices, and norms.